The effect of heat stress on humoral immnuity in broyler chickens - H. Hüseyin Hadimli; Kürşat Kav; Osman Erganiş (Eurasian Journal of Veterinary Sciences)
In this study, the effect of heat stress on humoral immunity against Newcastle (ND) and Infectious Bronchitis (IB) antigens was determined in broiler chicken after vaccination of ND and IB. Totally, 40 broiler chicks were divided into 2 groups as experimental and control. The broilers were mucosally and orally vaccinated with ND and IB vaccines at 1 and 17 days, respectively. Then they were treated at 38-39°C of heat stress between 15th and 30th days. Blood samples were collected from experimental groups at 10 days intervals, after vaccination. The titres of antibodies were determined against ND by Haemagglutination-lnhibition (HI) test and IB by ELISA. Decreased titres of antibodies against ND and IB antigens at 40 days samples were statistically found to be important in animals treated heat stress than controls.